Pendidikan pemakai : Perubahan prilaku pada siswa madrasah dalam sistem pembelajaran berbasis perpustakaan - Ade Abdul Hak (Pusat Perpustakaan UIN Syarif Hidayatullah Jakarta, 2004)
The existence of curriculum innovation is to be followed by improving student's behaviors, especially the skill of retrieving information for their studies. Library as a teaming resource in 'madrasah', where the atmospheres need information, is still hard to be used effectively. So, there is a demand to gain it throughout 'library instruction' in using library services because without having knowledge and skill to use them, they must have any difficulties, and all of these will continue to the lack of the successful of gaining competencies in learning process. Key Words: User Education; Behavior; Madrasah.